2005
DOI: 10.1111/j.1525-1497.2005.0163.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exam-room computing on clinician-patient communication

Abstract: Objective: To evaluate the impact of exam‐room computers on communication between clinicians and patients. Design and Methods: Longitudinal, qualitative study using videotapes of regularly scheduled visits from 3 points in time: 1 month before, 1 month after, and 7 months after introduction of computers into the exam room. Setting: Primary care medical clinic in a large integrated delivery system. Participants: Nine clinicians (6 physicians, 2 physician assistants, and 1 nurse practitioner) and 54 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(204 citation statements)
references
References 20 publications
9
194
0
1
Order By: Relevance
“…Negative EHR-related behaviors, such as poor eye contact and prolonged screen gazing, can undermine patient-centered communication [2,5]. Conversely, when communication is patient-centered, patient outcomes, understanding, and adherence to treatment, and cost utilization can improve [6].…”
Section: Introductionmentioning
confidence: 99%
“…Negative EHR-related behaviors, such as poor eye contact and prolonged screen gazing, can undermine patient-centered communication [2,5]. Conversely, when communication is patient-centered, patient outcomes, understanding, and adherence to treatment, and cost utilization can improve [6].…”
Section: Introductionmentioning
confidence: 99%
“…29,30,50 Eight studies described variation in the amount and manner in which the EMR was used. 15,36,39,41,46,48,51,54 Four studies examined typing behaviors 33,37,42,48 and six reported on screen positioning, with only 8-10 % active screen sharing during the visit. 29,30,33,37,38,52 Interestingly, one study noted patients had a more positive attitude towards the EMR when they were shown the screen.…”
Section: Characterizing Emr Communication Behaviorsmentioning
confidence: 99%
“…Finally, organizations can support an equal power dynamic for SDM by arranging computers in the exam room to be visible to both clinicians and patients. [99][100][101][102][103] …”
Section: Physical Environment: Welcoming Visual Cuesmentioning
confidence: 99%